Utilization of oyster shell waste (crassostrea gigas) as a source of calcium in hydroxyapatite synthesis - Irhamni, Irhamni; Juliana, Eka; Zulfalina, Zulfalina; Fauzi, Fauzi; Jalil, Zulkarnain (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
Biomaterials are materials that interact with living tissues for the purpose of treating and replacing tissues either temporarily or permanently. Biomaterials can be developed from hydroxyapatite-based materials. The source of calcium for the manufacture of hydroxyapatite is obtained from oyster shell waste (Crassostrea gigas) from the waters of Alue Naga Banda Aceh. The purpose of this study was to examine the opportunity to utilize oyster shell waste as a source of calcium for hydroxyapatite synthesis. The hydroxyapatite synthesis process was carried out by calcining oyster shells at a temperature of 10000C for 5 hours to obtain calcium oxide (CaO) content. Then, the CaO powder was reacted with phosphoric acid (H3PO4) to obtain hydroxyapatite compound (Ca10(PO4)6(OH)2) and then sintered at 900C for 2 hours. Analysis of CaO and hydroxyapatite phases was carried out through XRD (X-Ray Diffraction) characterization results. Surface morphology and element content were obtained from SEM-EDS characterization. Based on the analysis, CaO and hydroxyapatite phases have been successfully formed and the surface morphology of hydroxyapatite crystal structure is not clearly visible because of the formation of agglomeration. Based on the elemental content test, the ideal Ca/P ratio has not been obtained. Based on the results of the research, oyster shell waste (Crassostrea gigas) from the waters of Alue Naga, in Syiah Kuala District, Banda Aceh City has the opportunity to be utilized as a source of calcium in hydroxyapatite synthesis and can be developed as a biomaterial.